12‐month outcomes of ranibizumab versus aflibercept for macular oedema in central retinal vein occlusion: data from the FRB! registry. Issue 4 (13th September 2021) - Niedzwiecki, Mateusz; Hunt, Adrian; Nguyen, Vuong; Mehta, Hemal; Creuzot‐Garcher, Catherine; Gabrielle, Pierre‐Henry; Guillemin, Martin; Fraser‐Bell, Samantha; Arnold, Jennifer; McAllister, Ian L.; Gillies, Mark; Barthelmes, Daniel
Abstract: Purpose: To compare 12‐month treatment outcomes of eyes receiving aflibercept or ranibizumab for macular oedema secondary to central retinal vein occlusion (CRVO) in routine clinical practice. Methods: 296 treatment‐naïve eyes receiving either aflibercept (171 eyes, 2 mg) or ranibizumab (125 eyes, 0.5 mg) for macular oedema secondary to CRVO were recruited retrospectively from centres using the prospectively designed FRB! registry. The primary outcome measure was the mean change in LogMAR letter scores of visual acuity (VA). Secondary outcomes included change in central subfield thickness (CST), injections and visits, time to first grading of inactivity, switching and non‐completion from baseline to 12 months. Results: Baseline VA (SD) was somewhat better in aflibercept‐ versus ranibizumab‐treated eyes (42.5 ± 25.5 letters versus 36.9 ± 26 letters; p = 0.07) with similar CST (614 (240) μm versus 616 (234) μm: p = 0.95). The 12‐month adjusted mean (95%CI) VA change was +16.6 (12.9, 20.4) letters for aflibercept versus +9.8 (5.5, 14.1) letters for ranibizumab (p = 0.001). The mean (95%CI) adjusted change in CST was significantly greater in aflibercept‐ versus ranibizumab‐treated eyes: −304 (−276, −333) µm versus −252 (−220, −282) µm (p < 0.001). Both groups had a median (Q1, Q3) of 7 (5, 9) injections and 10 (8, 13) visits. Aflibercept‐treated eyes became inactive sooner than ranibizumab (p = 0.02). Switching occurred more commonly from ranibizumab (26 eyes, 21%) than from aflibercept (9 eyes, 5%) (p < 0.001). Conclusion: Both aflibercept and ranibizumab improved VA and reduced CST in eyes with CRVO in routine clinical practice, with aflibercept showing significantly greater improvements in this comparative analysis.